The Most Important Legal Solutions of Islamic Republic of Iran in Responding the Assassination of Martyr Lieutenant General Qassem Soleimani - mahnaz rasihidi; Ali Mashhadi (پژوهش تطبیقی حقوق اسلام و غرب, 2020)
After assassination of Major General Qassem Soleimani on January 2020 by the USA, an issue that arose between Iranian and international jurists from the beginning was the legal response of the Government of the Islamic Republic of Iran to the incident. This key question came to mind that which legal response to US illegal action should or can take place? In this regard, numerous opinions and guidelines were put forward by national and international jurists. Lodging Complaint in international judicial bodies, putting forward the criminal responsibility of the perpetrators, self-defense, reprisal and countermeasure, putting forward the US government's international responsibility before International Court of Justice, lodging complaint before national courts and employing human rights means to condemn US were the most important ones among these guidelines. This paper attempts to examine these legal responses within the context of existing international law and national legal rules of Iran and Iraq. The basic presumption of this article in answering the main question is that among the legal remedies available in the current circumstances lodging a complaint in International Court of Justice seems more appropriate.